Social norms, political polarization, and vaccination attitudes: Evidence from a survey experiment in Turkey - Mustafa Kaba; Murat Koyuncu; Sebastian O. Schneider; Matthias Sutter (Max Planck Institute for Research on Collective Goods, 2023)
This paper examines the role of social norms and political polarization in shaping vaccination attitudes and behaviors in the context of the Covid-19 pandemic. Using a largescale representative survey experiment in Turkey, we first show that political affiliation is a strong predictor of attitudes towards vaccination. We then use standard economic games to measure the extent of polarization caused by subjects' attitudes towards vaccination. We find that pro- and anti-vaxxers discriminate each other substantially. Furthermore, when pro- and anti-vaxxers perceive a political difference between them, this polarization is exacerbated. Finally, using randomized informational treatments, we show that the promotion of a broadly shared social identity might mitigate this outgroup discrimination.
hdl:21.11116/0000-000D-7524-7
Keywords: C9; D01; D9; 330; Impfung; Meinung; Soziale Norm; Experiment; Türkei